Device-related pressure ulcers from a biomechanical perspective. Issue 1 (February 2017) - Levy, Ayelet; Kopplin, Kara; Gefen, Amit
Abstract: Pressure ulcers (PUs) in the pediatric population are inherently different from those in adults, in their risk factors and etiology, with more than 50% of the cases related to contact with medical equipment at the care setting. The aims of this study were to: (i) Determine the mechanical loads in the scalp of a newborn lying supine, near a wedged encephalogram electrode or wire, which is deforming the scalp at the occiput. (ii) Evaluate the effect of a doughnut-shaped headrest on the mechanical state of tissues at the same site. We used finite element computational modeling to simulate a realistic three-dimensional head of a newborn interacting with the above devices. We examined effective (von Mises) stresses, shear stresses and strain energy density (SED) in the fat and skin tissues at the occipital region. The interfering wire resulted in the worse mechanical conditions in the soft tissues, compared to the lodged electrode and use of a doughnut-shaped headrest, with 345% and 50% increase in effective stresses in skin and fat tissues, respectively. Considering that elevated and localized tissue deformations, stresses and SED indicate a risk for PUs, our simulations suggest that misplaced medical devices, and using a doughnut-shaped headrest, impose an actual risk for developing device-related PUs. We conclude that guidelines for pediatric clinical care should recommend routine inspection of the medical device placement to prevent harmful contact conditions with the patient. Furthermore, improved design of medical equipment for pediatric settings is needed in order to protect these fragile young patients from PUs.